STUDI KASUS KONDISI RADIATOR PADA PERFORMA MESIN SISTEM PENDINGIN MELALUI KOMPUTASI DINAMIK FLUIDA DI PLTD BATAKAN - Lestari, Dwi Mardika; Kurniawan, M. Arief (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2022)
Computational fluid dynamics (KDF) is a commonly used method to solve physics cases that have the advantage of reducing operating costs, especially in the study of cooling systems in engines. In this study, the engine cooling system observed was located at the Diesel Power Plant (PLTD), Batakan. The cooling system on the engine has several important components that affect performance, one of which is the radiator. The condition of the radiator is observed with different fin designs, namely ideal conditions with fins (100%), 75%, and 50%. KDF helps to provide a detailed analysis of the performance of the engine cooling system. Under ideal conditions, the value of the temperature difference between the inlet and outlet in high temperature (HT) and low temperature (LT) pipes is 220C. From this study gave results, the condition of the radiator fins that were not ideal resulted in a decrease in temperature difference between the inlet and outlet in the HT and LT pipes.